Active aging needs from the perspectives of older adults and geriatric experts: a qualitative study - Ayoubi-Mahani, Shahla; Eghbali-Babadi, Maryam; Farajzadegan, Ziba; Keshvari, Mahrokh; Farokhzadian, Jamileh (Frontiers in Public Health, 2023)
Introduction With an increasing rate of population aging and its consequences, preparation for active aging based on older adults' needs is an unavoidable priority. Active aging needs must be identified to help strategic planning for older adults' health and wellbeing. This study aimed to explore the active aging needs from the perspectives of older adults and geriatric experts. Methods This exploratory-descriptive qualitative study was conducted in four provinces with the oldest populations in Iran. Semi-structured and focus group interviews were conducted with 41 participants (20 older adults and 21 geriatric experts), who were chosen through purposive and snowball sampling. Data were analyzed using the conventional content analysis. Results This study identified three themes and thirteen categories from the data: (1) basic individual needs with three categories of physiological, psycho-emotional, and spiritual needs; and (2) managerial needs with seven categories of political-legal, socio-economic, and cultural-spiritual infrastructures, academic strategies, an age-friendly environment; technological services, and provision of specialized services and daycare for older adults, and (3) educational needs with three categories of training self-care and self-efficacy, empowering the health care workers; and empowering the family. Conclusion The results revealed personal, managerial, and educational needs for active aging and could assist policymakers and geriatric experts to promote and meet active aging needs successfully.